Effect of Nutmeg (Myristica Fragrans) Methanolic Extract to the Growth of Dental Plaque Bacteria - Dewi Rosmalia; Minarni; Mhd Riza Marjoni (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2022)
Background: One of the causes of dental caries is Streptococcus mutant bacteria which has the ability to change the sugar content of food waste into lactic acid as the initial process of caries. One of the efforts to overcome dental caries is to use natural ingredients such as nutmeg. Every part of nutmeg has active substances that are efficacious as antimicrobial, antibacterial, antioxidant, antifungal and anti-inflammatory. Pulpam, seeds and fuli of nutmeg showed as potential extracts in inhibiting the growth of Streptococcus mutans. Objective: This study aimed to analyze methanol extracts from pericarpium, pulpam, fuli and nutmeg seeds against the growth of Streptococcus mutans bacteria that causes dental plaque. Methods: The research was conducted by diffusion method using BHI agar media and incubated anaerobically at 37°C for 24 hours. Results: The results of the calculation of the average diameter of the inhibition zones from the extract of fuli, seeds, pulpam and pericarpium of the nutmeg plant were 19.00 mm, 25.33 mm, 15.66 mm, 22.66 mm, and 21.83 mm, respectively. Data analysis using ANOVA (one way) showed that there were significant differences in all groups at p<0.05. The results of the LSD test showed that there were significant differences in all treatment groups. Conclusion: Methanol extract from fruit and fruit parts of nutmeg showed the ability to inhibit the growth of bacteria that cause dental plaque.